WOMEN: PERSPECTIVES FROM WORLD RELIGIONS - Thottakara, Augustine (Journal of Dharma, 2001)
"Women: Perspectives from World Religions" is the general theme of this issue of Journal of Dharma. Much has been written on this subject. In the past Journal has brought out some issues on topics related to women. This theme definitely needs further discussion, deliberation, conscientization and mobilization of resources for the actualization of positive programmes for the betterment of the lot of women. ’It is a matter of fact, a truth of history and a phenomenon of our daily experience that women are eminently tuned to a more intense form religious worship and spiritual life than men. They involve themselves with ease and enthusiasm in all internal and external acts of religiosity. It is mainly women who keep alive the faith in the family. They inculcate the faith, religious practices and traditions, customs and religious culture to the succeeding generation. The religious ethos and character of the family and of the society are generated, maintained and guaranteed mainly because of the uncompromising religiosity of women. Thus, their contribution to spirituality, collective religiosity and religious culture of their religion is immense. They maintain close relationship with the church, temple or shrine and actively participate in the rituals, worship, feasts and celebrations. Therefore, it is also a matter of fact that without the active help, participation and involvement of women in religious matters, no religion can effectively bear witness to its values and worth, carry out its mission and message and maintain its vigour and vitality.’